From street network topology to generic accessibility indices: Supraposition of Graph theory measures on morphological localities - Kopp Lukas; Rypar Vit; Havlova Zdenka (Lodz University of Technology Press, 2023)
Spatial analysis of street network accessibility has been widely utilised by academics and urban designers. However, when assessing the overall accessibility performance of larger morphologically consistent units – the urban localities – the results articulated on the street network are potentially problematic to interpret and generalize. This paper presents an innovative approach to the synthesis of various street network accessibility measures in the form of generic accessibility indices projected to various morphological localities. It determines a method specifically suitable for Prague urban tissues and it further explores the possible application of these indices in urban design and planning. Its objectives are (1) to identify and describe the spatial accessibility of public space and morphological characteristics of street spaces using network analysis; (2) to establish and assess accessibility indices for morphologically distinctive localities; (3) to examine the correlation between the accessibility indices of individual localities and their time of origin, providing valuable insight into the process of city evolution. The configurative analysis is carried out on a detailed street network within the administrative borders of Prague. Accessibility variables are then superposed on existing morphological localities delimited accordingly to the Conzenian tradition of urban morphology. Methods stemming from system ecology and descriptive statistics are utilised to provide control over the aggregation of the original variables into the generic accessibility indices while preserving sufficient descriptiveness. The results provide a valuable reference for various accessibility indices evaluation options in relation to the choice of statistical calculation and variables.
Keywords: urban accessibility; network centrality; urban morphology; urban morphometrics; cluster analysis; dostępność miast; centralność sieci; morfologia miast; morfometria miast; analiza skupień